A new species of Apiaceae (Pimpinella silvicola) from Tanzania. Issue 4 (December 2015) - Hemp, Andreas
Summary Pimpinella silvicola Hemp, a new species of Apiaceae (Umbelliferae), is described and illustrated from Tanzania.